NASIONALISME MASYARAKAT PERBATASAN DI KALIMANTAN BARAT INDONESIA - Elyta Elyta, Abi Sofyan, Ishaq Rahman, Ully Nuzulian (Mandala: Jurnal Ilmu Hubungan Internasional, 2018)
The nationalism of the border community is alleged to be a problem due to the activities of those who depend on Malaysia This study applies descriptive qualitative methods in analyzing the conditions of nationalism on the West Kalimantan border which is focused on the Sajingan Besar border area. The results of the study on the Sajingan Besar Sambas region showed two results from the point of view of nationalism conditions which refer to nationalism indicators, namely: (1). National identity, (2). The role of government in increasing national awareness; (Greenfeld, 1992: 3). (1). The identity of the Sajingan Besar border community, based on the awareness, identity and ideology of border communities while the border community depends on Malaysia and requires access to and out of the country and influences the dominant purchase of Malaysian products tends; (2). The role of the government in increasing national awareness, the dependence of border communities is due to weak development while the Malaysian border is already fairly developed.